Migration and activity of the eastern black-backed jackal (Canis mesomelas schmidtii) in Ol Pejeta, Kenya - Hedman Wallin, Julia (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
This study examined the effects of weather during the day and illumination at night on the migration activity of the eastern black-backed jackals (Canis mesomelas schmidtii) in Ol Pejeta, a wildlife conservancy in Kenya, from October 2015 to December 2019. Jackal ecology is an understudied subject where focus has been directed to a sub-specie of black-backed jackals in southern Africa, with different animals, seasons, and habitats than to those in Ol Pejeta and eastern Africa. Black-backed jackals are important mesopredator in areas they live in and can even be beneficial to livestock farmers due to their ability to supress certain herbivore populations. Migration activity was investigated by using camera trap footage from three wildlife corridors along the northern conservancy boarder. Jackals were found active between 19:00 to 06:00 with two activity peaks, and observations found jackals to be active inside the conservancy during low activity hours at the corridors. Daily average temperature, cloud cover and rainfall were ranked into 3 categories from low, medium to high and were found to be significant together for corridor activity (p = 0.016, p = 0.009 and p < 0.001). Temperature as a factor alone did not show any significance activity changes between the 3 ranks (p = 0.124) but activity increased slightly percentwise with increased temperatures. However, both cloud cover and rainfall significantly (p < 0.001 & p < 0.001) decreased activity with higher amount of cloud cover and rainfall. Illumination from the moon at nights did have a significant effect (p = 0.024) on jackal activity where activity was significant (p = 0.021) between 5 ranks, while cloud cover did not (p = 0.756), Only the ranks between new moon and full moon showed a significant (p = 0.008) activity increase. These results provide a much needed and updated insight into jackal ecology, as well as to increase the already lacking research on the eastern black-backed jackal.